Nodular fasciitis on the cheek of a child. Issue 2 (6th January 2021) - Patel, Deep; Samson, Thomas D.; Cochran, Eric L.; Zaenglein, Andrea L.
Abstract: Nodular fasciitis is a benign proliferation of myofibroblastic cells affecting subcutaneous tissue, muscles, and fascia. This rare disorder is most commonly observed on the upper extremity of adults. We present a case of nodular fasciitis of the cheek of a 12‐year‐old girl.